Financial sustainability of NGOs in rural development programmes. Issue 3 (3rd April 2021) - Shava, Elvin
ABSTRACT: This article assesses the challenges facing both local and international NGOs in Mwenezi district of Zimbabwe in their efforts to ensure financial sustainability. Drawing from a qualitative approach that employs interviews and documents, the study revealed that reduced funding from the donor community, changing priorities of funders, poor resource allocation and lack of transparent structures to attract donor funding impact on the financial sustainability of NGOs. To ensure their financial sustainability, NGOs must do away with the donor dependency syndrome and embark on other entrepreneurial and strategic fundraising strategies.